Decreased Serum Brain-Derived Neurotrophic Factor Concentrations 72 Hours Following Marathon Running - Roeh, Astrid; Holdenrieder, Stefan; Schoenfeld, Julia; Haeckert, Jan; Halle, Martin; Falkai, Peter; Scherr, Johannes; Hasan, Alkomiet (Frontiers in Physiology, 2021)
Background Physical exercise has been linked to beneficial effects on brain plasticity. One potential key mechanism for this relationship is an exercise-induced increase of Brain Derived Neurotrophic Factor (BDNF). However, the kinetics of BDNF in athletes during training phase, extreme exercise competition and recovery period have not been investigated so far. Methods We assessed serum BDNF levels concentrations in 51 marathon runners (23 % female, mean age 43 years) in a longitudinal study design over a period of six months. Assessments were conducted during the training period before the marathon, after the marathon race and during short (24 to 72 hours) and long-term (3 months) follow-ups. Potential confounders (fitness level, sex, platelet count) were included in subsequent linear-model analyses. Results Repeated-measures ANOVA revealed a main effect of time for BDNF levels concentrations over the study period (F(5,250)=15.986, p<0.001). The highest BDNF levels concentrations compared to baseline were observed immediately after the marathon (p=0.070, trend). Values decreased significantly thereafter with the lowest values at 72 hours after the marathon (p<0.001), a finding that was more pronounced in the larger male cohort. Conclusion Prolonged exercise induces an increase in BDNF levels concentrations with a significant rebound effect after 72 hours post exercise. We hypothesize that the decrease of BDNF is mainly driven by regenerative mechanisms and a higher muscular utilization.